Experiences, Motivations, and Perceived Impact of Participation in a Facebook-Based Support Group for Caregivers of Children and Youth With Complex Care Needs: Qualitative Descriptive Study - Katherine Jennifer Kelly; Shelley Doucet; Alison Luke; Rima Azar; William Montelpare (JMIR Publications, 2022)
BackgroundCaregivers of children and youth with complex care needs (CCNs) often require considerable support to ensure the well-being of their families. Social media present an opportunity to better support caregivers through computer-mediated communication for social support. Peer-to-peer (P2P) support groups are a way in which caregivers are accessing needed support; however, the experiences of caregivers who use these groups and the perceived impact that participation has on caregivers of children and youth with CCNs are not known. ObjectiveThis study aimed to explore the experiences of caregivers of children and youth with CCNs who use a Facebook-based P2P support group to communicate, understand their motivations to use the group, and investigate its perceived impact on knowledge of programs and services and sense of community belonging among caregivers. MethodsA qualitative descriptive design was used to explore the experiences and perceived impact of a Facebook-based (Meta Platforms) P2P support group for caregivers of children and youth with CCNs in New Brunswick, Canada. The group was launched on the web in October 2020, during the COVID-19 pandemic, and resulted in 108 caregivers joining the group. A web-based survey was distributed, and semistructured interviews were conducted in February 2021 with a subsample of members. Thematic analysis was used to identify and report patterns related to caregivers' experiences and perceived impacts of participation. ResultsA subsample of members in the Facebook group completed the web-based survey (39/108, 36.1%) and interviews (14/108, 12.9%). A total of 5 themes emerged from the interviews: safe space, informational support and direction, web-based connection with peers, impact on knowledge of programs and services, and degree of community belonging. Participants reported joining the group to obtain geography-specific information support and connect with peers. Many participants reported an improvement in their knowledge of programs and services and felt connected to the community; however, the short observation period and diversity among the caregiver population were cited as barriers to community belonging. ConclusionsSocial media present an important opportunity to facilitate the exchange of support between patients and caregivers in an accessible and curated environment. Findings from this study suggest that involvement in web-based, geography-specific P2P support groups can influence perceived knowledge of services and resources and sense of community belonging among caregivers of children and youth with CCNs. Furthermore, this study provides insight into the experiences and motivations of caregivers of children and youth with CCNs who participate in a private social media environment.